Risk factors for spatial memory impairment in patients with temporal lobe epilepsy - Amlerova, Jana; Laczo, Jan; Vlcek, Kamil; Javurkova, Alena; Andel, Ross; Marusic, Petr (Epilepsy & behavior, 2013)
At present, the risk factors for world-centered (allocentric) navigation impairment in patients with temporal lobe epilepsy (TLE) are not known. There is some evidence on the importance of the right hippocampus but other clinical features have not been investigated yet. In this study, we used an experimental human equivalent to the Morris water maze to examine spatial navigation performance in patients with drug-refractory unilateral TLE. We included 47 left-hemisphere speech dominant patients (25 right sided; 22 left sided). The aim of our study was to identify clinical and demographic characteristics of TLE patients who performed poorly in allocentric spatial memory tests. Our results demonstrate that poor spatial navigation is significantly associated with younger age at epilepsy onset, longer disease duration, and lower intelligence level. Allocentric navigation in TLE patients was impaired irrespective of epilepsy lateralization. Good and poor navigators did not differ in their age, gender, or preoperative/postoperative status. This study provides evidence on risk factors that increase the likelihood of allocentric navigation impairment in TLE patients. The results indicate that not only temporal lobe dysfunction itself but also low general cognitive abilities may contribute to the navigation impairment.
Keywords: Electroencephalography; Male; poruchy paměti; Risk Factors; magnetická rezonanční tomografie; Maze Learning; elektroencefalografie; Adult; dospělí; mužské pohlaví; Neuropsychological Tests; bludiště - učení; Intelligence; lidé; ženské pohlaví; funkční lateralita; Humans; inteligence; Functional Laterality; rizikové faktory; prostorové chování; Epilepsy, Temporal Lobe; neuropsychologické testy; Magnetic Resonance Imaging; Spatial Behavior; Female; Memory Disorders; epilepsie temporálního laloku